Using the eating disorder examination to identify the specific psychopathology of binge eating disorder. - Wilfley, D; Schwartz, M; Spurrell, E; Fairburn, C (2000)
OBJECTIVE: The clinical features of binge eating disorder (BED) are not well established. Therefore, a comprehensive assessment of the specific psychopathology of BED as compared to anorexia nervosa (AN) and bulimia nervosa (BN) is warranted. This comparison was the aim of the present study. METHOD: Detailed ratings from an investigator-based interview, the Eating Disorders Examination (EDE), were compared across three groups of female patients: those with BED, AN, and BN, as well as normal-weight and overweight control subjects. RESULTS: When comparing BED to AN and BN, patients with BED had lower levels of restraint, eating concerns comparable to AN patients but lower than BN patients, and weight and shape concerns comparable to BN patients but higher than AN patients. Significantly more eating disorder psychopathology was found for BED patients as compared to the overweight controls on all bar the EDE restraint subscale. On the majority of individual EDE items, BED patients' scores were similar to those of AN and BN patients, including importance of shape and weight in self-evaluation and preoccupation with shape and weight. No significant relationship was found between BED patients' degree of overweight and eating psychopathology. DISCUSSION: Our findings support the status of BED as an eating disorder and suggest that the elevated EDE scores reflect the combined impact of being objectively overweight and having disordered cognitions and behaviors about eating, shape, and weight.